EEG analysis of opioid-dependents during methadone maintenance / Fatemeh Molaei Vaneghi - Fatemeh , Molaei Vaneghi (2012)
This study aims to explore the structural brain changes in heroin abusers after the first administration of methadone and therefore examine the role of methadone in normalizing the psychophysiological impairments associated with the state of opioid dependency. The ability of methadone to restore the normal cortical functioning in opioid dependents the composition of electroencephalographic (EEG) oscillations within a broad frequency band (0.5Hz – 60Hz) was explored. The Independent Component Analysis (ICA) was used to identify the cortical regions and their relevant spectro-temporal activities involved in opioid dependency and methadone therapy based on the information content of the scalp EEG signal. It has been shown that within the state of opioid dependency the majority of brain activities responsive to opioids are located within the medial prefrontal cortex (mPFC) and the extended limbic system, and these activities reduced significantly after methadone administration. Spectral activities of the brain within alpha, beta, and gamma frequencies increased during opioid dependency while, unlike the gamma spectrum, the alpha and beta spectral activities underwent a decline early after the onset of methadone administration.